2016
DOI: 10.1002/rcs.1779
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, controlled trial of robot‐assisted vs freehand pedicle screw fixation in spine surgery

Abstract: Robotic-assisted pedicle screw placement was associated with fewer proximal facet joint violations and better convergence orientations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
246
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(256 citation statements)
references
References 22 publications
7
246
3
Order By: Relevance
“…2,5,6,9,[11][12][13][14][15]17,21,22,24,25,[27][28][29][30][31][35][36][37] Twenty-one of these studies used variations of the robot developed by Mazor, whereas 1 study evaluated the ROSA robot. Twenty-one studies evaluated pedicle screw accuracy, whereas Dreval et al evaluated both pedicle screws and guided oblique lumbar interbody fusion (GO-LIF) screws, 6 and Bederman et al evaluated the accuracy of S2-alar-iliac screw placement.…”
Section: Accuracy Of Spinal Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations
“…2,5,6,9,[11][12][13][14][15]17,21,22,24,25,[27][28][29][30][31][35][36][37] Twenty-one of these studies used variations of the robot developed by Mazor, whereas 1 study evaluated the ROSA robot. Twenty-one studies evaluated pedicle screw accuracy, whereas Dreval et al evaluated both pedicle screws and guided oblique lumbar interbody fusion (GO-LIF) screws, 6 and Bederman et al evaluated the accuracy of S2-alar-iliac screw placement.…”
Section: Accuracy Of Spinal Instrumentationmentioning
confidence: 99%
“…31 Onen et al described an FT of 1.3 seconds per screw, whereas Kim et al described a total FT of 20.4 seconds. 15,24 Roser et al evaluated both standard navigation and freehand techniques in comparison with robotically placed screws. 28 They reported that FT and radiation dosage were lowest in the standard navigation group, followed by the robotic group.…”
Section: Radiation Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…2). 20,24 Cranial applications for these robots include stereotactic deep brain stimulator placement, laser thermal ablation therapy, tumors, and endoscope navigations. 6,8,18,56 In cranial surgeries, the preoperative MRI is merged with the intraoperative CT or MRI scan.…”
Section: 45mentioning
confidence: 99%